Managing Common Interventional Radiology Complications A Case Based Approach - Ratnam, Lakshmi; Patel, Uday; Belli, Anna Maria (Springer London : Imprint: Springer, 2014)
Managing Common Interventional Radiology Complications: A Case Based Approach is an easy-to-use manual that will help trainees and practising radiologists by providing cases which cover most of the complications that a general interventionalist may encounter in normal practice. The cases are presented succinctly but thoroughly, so that the reader is equipped to manage the complication immediately. Managing Common Interventional Radiology Complications: A Case Based Approach aims to teach the range of procedures involved in interventional radiology, and focuses on the complications that can arise in the process.